Managed aquifer recharge via infiltration ditches in short rotation afforested areas. Issue 1 (16th March 2015) - Mastrocicco, M.; Colombani, N.; Salemi, E.; Boz, B.; Gumiero, B.
Abstract: Managed aquifer recharge design and operation must incorporate the expected long‐term performance from a water quantity perspective to sustainably mitigate hydrologic impacts of groundwater overexploitation. Gravity‐driven infiltration ditches in forested areas are one of many managed aquifer recharge schemes that could augment the available water resources. Research on the longevity of these structures is sparse, leading to concerns about their long‐term capability to sustain elevated infiltration capacity. In the present study, an infiltration system consisting of a regular grid of eight ditches divided into four sequential plots within a short rotation forested area [area of infiltration (AFI)] was monitored from its inception to determine its hydrologic performance over time and its possible export to similar areas of the Brenta megafan (Northern Italy). During the monitored period, the AFI was not significantly affected by clogging because the suspended solids carried by the Brenta River water diversion were extremely low. The main source of clogging was the fallen foliage during the autumn, easily managed via ordinary maintenance. The AFI displayed an almost constant performance to infiltrate the diverted water over the first 3 years of operation, with a total amount of infiltrated water of approximately 0.8 Mm 3 ha −1 year −1 . The best tracer to reconstruct the downward water movement through this highly permeable vadose zone was temperature, while the groundwater table fluctuation could not be confidently used to infer the effective infiltration, because of its large seasonal variability. The good results suggest promoting this technique in other areas of the Brenta megafan that suffer from groundwater resources depletion. Copyright © 2015 John Wiley & Sons, Ltd.